The Good Corporate Governance (GCG) as a Moderating Factor in the Influence of Asset Management and Capital Structure on Financial Performance - Yusnindar, Yusnindar (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
The purpose of this study is to determine the impact of asset management and capital structure on financial performance moderated by good corporate governance, in food and beverage issuers verified on the Indonesia Stock Exchange in 2020 to 2024. The study population consisted of 90 companies, with sample selection carried out through purposive sampling, resulting in 25 samples according to the criteria. The analytical method used was panel data regression analysis with the help of Eviews version 12.0. The findings of this research reveal that asset management and capital structure have a positive and significant effect on financial performance. Good Corporate Governance can moderate the effect of asset management on financial performance in a significant positive way, but cannot moderate the impact of capital structure on financial performance in a significant positive way.